The Influence of Just Culture and Organizational Culture on Awareness of Incident Reporting Behavior - Ludiwyk Ludiwyk; Bayu Wahyudi; Rinawati Rinawati (Newinera Publisher, 2025)
This study aims to determine the influence of Just Culture and organizational culture on the awareness of incident reporting behavior by healthcare workers at Siloam Hospital Banjarmasin. The study used a quantitative approach with a survey method through questionnaires and documentation, and involved 88 respondents. Data were analyzed using descriptive analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression analysis, and hypothesis testing (t-test and F-test) and the coefficient of determination. The results showed that Just Culture and organizational culture have a significant influence on incident reporting behavior by healthcare workers at Siloam Hospital Banjarmasin. The regression coefficient value for Just Culture is 0.830 with a significance of 0.000, while organizational culture has a coefficient of 0.241 with a significance of 0.025, both of which are smaller than 0.05. This indicates that increasing Just Culture and organizational culture will positively increase incident reporting behavior. Multiple linear regression analysis produces the equation Y = 3.283 + 0.830 X1 + 0.241 X2, and the coefficient of determination (R Square) value is 0.506, which means that more than half of the variation in incident reporting behavior can be explained by both variables simultaneously. The F test also shows a significance of 0.000, confirming the joint influence of Just Culture and organizational culture on incident reporting behavior. This finding emphasizes the importance of strengthening both cultures in increasing awareness and actions of incident reporting in the hospital environment.